2019
DOI: 10.1590/1980-265x-tce-cicad-1-10
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Use of Alcohol, Marijuana and Cocaine and the Sociodemographic Characteristics of University Students of Ribeirão Preto, Brazil

Abstract: Objective: to determine the prevalence of use in life and in the last three months of alcohol, marijuana and cocaine among university students from the social and health Sciences areas of Ribeirão Preto, Brazil and to evaluate the association between use in life and in the last three months of alcohol, marijuana and cocaine and the variables gender, area of the course, with whom the student lives, importance of religion, age and year of study. Method: a cross-sectional study, carried out with a convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
1
6
1
8
Order By: Relevance
“…On the other hand, more time spent outside class studying was associated with a lower chance of using the three substances, and other studies have also found that on days when students spent more time studying, fewer heavy drinking episodes were reported (25) . Religious movements, on the other hand, were associated with a 72%, 76.5% and 81.2% reduction in the chances of alcohol, tobacco and illicit drug use, respectively, corroborating the findings in the literature (26)(27) .…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, more time spent outside class studying was associated with a lower chance of using the three substances, and other studies have also found that on days when students spent more time studying, fewer heavy drinking episodes were reported (25) . Religious movements, on the other hand, were associated with a 72%, 76.5% and 81.2% reduction in the chances of alcohol, tobacco and illicit drug use, respectively, corroborating the findings in the literature (26)(27) .…”
Section: Discussionsupporting
confidence: 87%
“…In 2010, a non‐representative sample of university students assessed by the Inter‐American Drug Abuse Control Commission showed a prevalence of 13.8% for past‐year cannabis use [61]. Regional (e.g., city or state) samples ( n = 52–9974) identified rates of 8%–42% for lifetime, 2%–44% for past‐year, 9%–18% for past 3 months, and 0.6%–23% for past‐month cannabis use between 1996 and 2021 [62–83].…”
Section: Resultsmentioning
confidence: 99%
“…No quesito do tipo de bebida alcoólica mais consumida, identifica-se maior prevalência para uso da cerveja, característica que se alinha a outras pesquisas (7,25,29) e também se associou aos perfis de consumo do AUDIT. Argumenta-se acerca do fácil acesso a esses tipos de bebidas, além de serem encontrados em todos os lugares e a preços baixos (4,(19)(20) .…”
Section: Discussionunclassified
“…O I Levantamento Nacional sobre o Uso de Álcool, Tabaco e Outras Drogas entre Universitários das 27 capitais brasileiras apontou que 86,5% da população universitária já experimentaram álcool alguma vez na vida, 60,5% declararam ter feito uso de álcool nos últimos 30 dias, 19,2% dos universitários preencheram os critérios para uso abusivo, e 2,6%, os critérios para uso de alto risco ou de dependência (3) . Assim, o uso de álcool representa a substância psicoativa mais utilizada entre os universitários (4)(5) e cuja prevalência é maior em comparação com a população em geral (89,3% versus 78,6%) (6) .…”
unclassified
See 1 more Smart Citation